Autonomy Development for Unmanned Aerial Vehicles with Jason Agents - Hama, Marcelo T.; Bordini, Rafael H. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2012)
Aerospace technology takes a very important role in several subjects and, in this context, unmanned aerial vehicles (UAV) are evolving into a noticeable theme where the application of agent designs, for autonomy development, has become a much used approach over the last decade. This paper presents an agent-oriented model to develop autonomy and to program UAVs with the use of Jason agents.